The external liquidity and solvency of Serbia - Vuković Vlastimir (Međunarodni Problemi)
The author explores the external liquidity and solvency of Serbia in the 2002-2005 period. He analyses four main groups of indicators concerning the external liquidity and solvency of Serbia: (1) indicators of external liquidity, (2) indicators of external solvency, (3) indicators of exposure the financial risks, and (4) the economy openness degree, which consist of ten most important indicators in international statistics. Comparing them with the indicators for the selected group of nine countries from the broader neighborhood the author gives an insight into the relative external position and rank of Serbia, additionally explaining the factors of its external liquidity and solvency. The results of the comparative analysis do not correspond to the usual meaning of the weak Serbian external position, while the indicators of financial safety are surprising for many experts.